PENGEMBANGAN APLIKASI MANAJEMEN ARSIP BERBASIS WEB DI KANTOR DESA CIHAURBEUTI - NAFISAH, MARSAA LUJAIN SITI (Universitas Lampung, 2025)
Abstract. Village-level archive management is a crucial aspect of village government administration, aimed at ensuring order, transparency, and accountability in data storage. However, archive management in villages is still largely carried out manually, often leading to various issues such as inefficiency, difficulties in document retrieval, and the risk of data loss. Cihaurbeuti Village faces similar challenges, necessitating a digital-based solution to enhance the effectiveness of archive management. This study aims to develop a web-based archive management application specifically designed to meet the administrative needs of the village. The system development follows the Agile methodology to ensure flexibility and quick adaptation to user needs. A case study was conducted in Cihaurbeuti Village, with system testing performed using the Black Box Testing method to ensure optimal functionality. The research findings indicate that the application can accelerate archive retrieval, reduce the risk of document loss, and improve administrative transparency in the village. With this system, archive management becomes more structured and efficient, supporting a more modern village governance system. The implementation of this system is expected to serve as a model for developing similar applications in other villages facing similar archive management challenges.